Дневник партизанских действий 1812 года - Давыдов Денис Васильевич (Гослитиздат, 1942)
Экземпляры: РК (20160319) / Инвентарный номер: д44879 / Цена: 1.00 / Сис.шифр: 9(С)15 / Авт.знак: Д 13 / ГРНТИ: 03 / ББК: 63